Development of a large capacity cryopump equipped with a two-stage GM cryocooler. (25th November 2022) - Park, Jiho; Ko, Junseok; Kim, Hyobong; Chu, Sangyoon; Kim, Jongwoo; Kim, Juwon; In, Sehwan; Hong, Yongju; Park, Seongje; Yeom, Hankil
Highlights: A 20-inch cryopump including a two-stage GM cryocooler has been developed. Design methodologies behind the GM cryocooler and cryopump have been addressed. The cooling capacities of the GM cryocooler exceed 80 W and 8 W at each stage. The pump captures N2 with 11, 000 L s −1 and endures gas impulse of 2, 500 mbar L. The pump can evacuate down to ultimate pressure of 10 -9 mbar-class. Abstract: Cryopump, which involves the removal of gas by cryo-sorption, condensation and solidification onto cryo-panels, is an ideal form of ultra-high vacuum (UHV) pump due to its contamination-free operation and black hole pumping speed. The high crossover of the cryopump can provide a clean vacuum environment. Since the cryopump utilizes the cryo-pumping effects mentioned above, a cryogenic environment is a prerequisite condition. In this research paper, a 20-inch cryopump, which is driven by a two-stage Gifford-McMahon (GM) cryocooler, is developed and tested. The GM cryocooler is designed by optimizing the opening timing of the rotary valve, and the corresponding thermal losses at its each stage have been analyzed. Under the thermal loads of 80 W and 8 W at each stage of the GM cryocooler, the temperatures are measured to be 66 K and 19.5 K, respectively. The cryopump is designed with the aspect of heat transfer assessment. The model described in this paper considers two major thermal loads; radiative heat ingress and enthalpy transfer by the existence of the gas. This simple model can readily predict the thermal loads on each stage of the GM cryocooler. Since all the cryo-panels are kept below 130 K during operation, the cryopump that has been developed is therefore compatible with a UHV pump. Using nitrogen gas, the ultimate pressure, pumping speed and crossover are measured to be 9.9 × 10 -9 mbar, 11, 000 L s −1 and 2, 500 mbar L, respectively. Through the experiments, it is also concluded that the numerical model above can explain the thermal characteristics of the cryopump reasonably well. The cryopump will be able to respond to the market needs of the large-size display and semiconductor manufacturing processes as well as increase its energy saving and process operability. Furthermore, the reliability of the GM cryocooler can also be improved through turndown operations.